Perspectivas em Aminas Biogênicas: ensaio translacional in vitro e in silico na interação do extrato da folha da Bergamota no Osteossarcoma - Botelho, Gabriela Abreu [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Introduction: Osteosarcoma is a highly malignant neoplasm that affects dogs and humans without predilection. The use of combined therapies in oncology and precision medicine is a reality in treatments. Bergamot leaf extract (Citrus bergamia) proves to be a valuable source of bioactive compounds that help with comorbidities situations. The use of infusions and extracts rich in bioactive compounds acts beneficially on organism by reducing inflammation and oxidative stress. Objective: Evaluate the interaction of this Extract on Canine and Human Osteosarcoma cells in vitro focused on cellular cytotoxicity and verify in silico the differentially expressed proteins present in Human Osteosarcoma, Canine Osteosarcoma and Control Bone Tissue. Material and methods: Cell culture of Canine Osteosarcoma (OSA7), Culture of Human Osteosarcoma Line MG-63 and Control Fibroblast Line 3T3-E1, different dosages of bergamot leaf extract applied to the samples. Cytotoxicity was assessed using the MTT and Neutral Red techniques. A 50% cell inhibitory concentration (IC50) study was carried out. In addition, in silico analyses evaluated the ratio of proteins present in Human Osteosarcoma and Control Bone Tissue, protein interaction networks with SPRING, comparison of Osteosarcoma proteins in terms of similarity of Positively Expressed Genes (UP Regulated) and pharmacological prediction of the Biogenic Amines contained in Extract via Molecular Docking. Results: Bergamot leaf extract showed different cell cytotoxicity indices in vitro on comparative osteosarcoma models, showing greater resistance on control fibroblast cells. The IC50 of the cells showed a statistically significant difference between the cell samples. The in silico studies showed separation of the tumor and control bone tissue samples, normalization and analysis of the different Up and Down DEG expression pathways, comparison of the positively expressed protein interaction networks and Molecular Docking of Biogenic Amines. Conclusion: In vitro treatment has cell growth inhibitory potential in the different lineages and showed low cytotoxicity to healthy fibroblast cells. In silico analyses show range of therapeutic possibilities in extract and good binding affinity by molecular docking of the biogenic amines in contact with an osteosarcoma target protein.

Introdução: O Osteossarcoma é uma neoplasia altamente maligna que afeta cães ehumanos sem predileções. O uso de terapias combinadas na Oncologia e a medicinadeprecisão é uma realidade nos tratamentos. O Extrato da folha da Bergamota, demonstravaliosa fonte de compostos bioativos atuantes no auxílio de diversas comorbidades. Ouso de infusões e extratos ricos em compostos bioativos atuam de forma benéficaaoorganismo reduzindo os índices de inflamação e estresse oxidativo. Objetivo: Avaliar ainteração do Extrato da Folha de Bergamota (Citrus Bergamia) sob células deOsteossarcoma Canino e Humano in vitro com enfoque na Citotoxicidade celular everificar via Bioinformática in silico as proteínas presentes no Osteossarcoma Humano, Canino e Tecido Ósseo controle diferencialmente expressas. Material e métodos: Realizada cultura primária de Ostessarcoma Canino (OSA7), Cultura da LinhagemMG- 63 de Osteossarcoma Humano e Linhagem de Fibroblasto controle 3T3-E1, aplicadasdiferentes dosagens do extrato de folha da bergamota nas amostras. Avaliadacitotoxicidade por técnica de MTT e Vermelho Neutro. Realizado estudodaconcentração inibitória de 50% das células (IC50). Adicionalmente, análises insílicoavaliaram a relação de proteínas presentes em Osteossarcoma Humano e Tecido Ósseocontrole, redes de interação proteicas via SPRING, comparação das proteínas dosOsteossarcomas em similaridade de Genes Positivamente expressos (DEG’s UPRegulados) e realização de predição farmacológica das Aminas Biogênicas do Extratovia Docking Molecular. Resultado: O Extrato da folha da Bergamota demostrou índicesde citotoxicidade celular diverso in vitro nos modelos comparativos do Osteossarcoma, demonstrando maior resistência nas células de Fibroblastos controle. Oíndicedeconcentração inibitória de 50% das células apresentou diferença estatística significantedentre as amostras celulares. Os estudos in sílico demonstraram separação das amostrasde tumorais e tecido ósseo controle, realizada normalização e análise das diferentes viasde expressão das DEG’s Up e Down, comparação das redes de interação proteicaspositivamente expressas e Docking Molecular das Aminas Biogênicas. Conclusão: Otratamento in vitro possui potencial inibitório de crescimento celular nas diferenteslinhagens e apresentou baixa citotoxicidade as células de fibroblastos saudáveis. Asanálises in silico demonstram uma gama de possibilidades terapêuticas para o Extratoeboa afinidade ligante por docking molecular das Aminas Biogênicas emcontatocomuma proteína alvo do Osteossarcoma.
New Perspectives on Biogenic Amines: in vitro and in silico translational assay on the interaction of Bergamot leaf extract in Osteosarcoma
Keywords: Osteossarcoma; Citrus bergamia; Bioinformática; Oncopatologia; Biogenic Amines; Oncopathology; Oncopathology